2016
DOI: 10.1002/cphc.201600467
|View full text |Cite
|
Sign up to set email alerts
|

Substituent‐Stabilized Organic Dianions in the Gas Phase and Their Potential Use as Electrolytes in Lithium‐Ion Batteries

Abstract: Using density functional theory and a hybrid exchange-correlation functional, a systematic study of the stability and electronic structure of neutral and multiply charged organic molecules, B C X (n=0, 1, 2; X=H, F, CN) and B C X (n=0, 1; X=H, F, CN) is performed. The results show that in addition to the aromaticity of the molecules, substituents play an important role in stabilizing the organic dianion complexes. In particular, it is demonstrated that CN groups are responsible for the stability of organic dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The stability of the dianion is further enhanced if such substitution is accompanied by substitution of C by B. Note that the dianion B 2 C 4 (CN) 6 is stable against electron emission by 1.10 eV . The second electron affinity of B 2 C 8 (CN) 8 (1.97 eV) is larger than that of B 2 C 4 (CN) 6 as it has more CN ligands.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The stability of the dianion is further enhanced if such substitution is accompanied by substitution of C by B. Note that the dianion B 2 C 4 (CN) 6 is stable against electron emission by 1.10 eV . The second electron affinity of B 2 C 8 (CN) 8 (1.97 eV) is larger than that of B 2 C 4 (CN) 6 as it has more CN ligands.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the dianion B 2 C 4 (CN) 6 is stable against electron emission by 1.10 eV. [15] The second electron affinity of B 2 C 8 (CN) 8 (1.97 eV) is larger than that of B 2 C 4 (CN) 6 as it has more CN ligands. Thus, one can use both ligand substitution and size as effective parameters to enhance the stability of multiply negatively charged organic molecules.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the most well-known dianions is B 12 H 12 2– closo -borane, , which is stable, in the gas phase, against spontaneous electron emission by 0.9 eV. Stability of these species is explained by the Wade–Mingos rule, which requires ( n + 1) pairs of electrons, where n is the number of vertices in the boron polyhedron. It was recently shown that the stability of these dianions could be substantially improved by ligand substitution. For example, B 12 (CN) 12 2– and B 12 (SCN) 12 2– are stable against electron emission by 5.3 and 3.3 eV, , respectively. This prediction has recently been confirmed experimentally and the measured second electron affinity of B 12 (CN) 12 2– , 5.55 eV, agrees well with the predicted value.…”
Section: Introductionmentioning
confidence: 99%